Community Empowerment Through Processing Cow Manure Into Compost Fertilizer - Yhasinta Agustyarini, M.Pd; Akhmad Fauzi; Benny Angga Permadi; Agung Purwono (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2023)
Indonesia is an agricultural country because most of the population works in the agricultural sector. The main need for farmers is fertilizer, to support plant growth properly. The relatively expensive price of fertilizer is an obstacle for farmers in Tawangrejo Village. The majority of the Tawangrejo Village community are farmers and have a large number of cattle, of course this can be used to produce compost. Therefore we are moved to empower the people of Tawangrejo Village regarding the production of compost from cow dung. The hope is that it can help the community in meeting their fertilizer needs, besides that compost production also has the potential to increase income for the community. This community service uses the Participatory Action Research (PAR) research method. The data contained in this paper were obtained from implementing a series of PAR methods supported by observation, interviews, and documentation. The results of this study are the emergence of public awareness to utilize cow dung as compost and the creation of a community group of compost producers in Tawangrejo Village.